The Effect Of Combining Liquid Organic Fertilizer (POC) And Vermicompost On Soybean (Glycine Max L. Merril) Production - Puspita, Diah Eka (Universitas Serambi Mekkah, 2025)
Abstract The Effect of Combination of Liquid Organic Fertilizer (POC) and Vermicompost Fertilizer on Soybean Production (Glycine max L. Merril).” The purpose of this study was to observe the Effect of Combination of Liquid Organic Fertilizer (POC) and Vermicompost Fertilizer on Soybean Production (Glycine max L. Merril).” The method used was a Randomized Block Design (RAK) arranged in a factorial manner with 2 factors applied to soybean plants, repeated twice. The first factor was the concentration of POC Been Sae with 4 treatment levels: P0 (control), P1 = 1 ml / 1 liter of water, P2 = 2 ml / 1 liter of water, and P3 = 3 ml / 1 liter of water. The dose of vermicompost fertilizer also had 4 treatment levels: K0 = control, K1 = 9 tons / 45 g / polybag, K2 = 18 tons / 90 g / polybag, and K3 = 27 tons / 135 g / polybag. The results of the study showed that the treatment of fertilizer concentrations P0 (control), P1 (1 m / L water), P2 (2 m / L water), P3 (3 m / L water) have significantly affect the number of seeds and dry seed weight of soybean plants. Vermicompost treatment significantly affected significantly for number of seeds and dry seed weight of soybean plants.